WAYS TO TEACH FUTURE TEACHERS TO THINK LOGICALLY THROUGH JAPANESE PUZZLES (Conferencea, 2024)
This article describes ways to train future teachers' logical thinking skills through Japanese puzzles. Based on the historical puzzle, students acquire the skills of searching for and separating the necessary information, establish cause-and-effect relationships, build a logical chain of reasoning, and choose and solve the most convenient and effective methods of solving the puzzle based on concrete conditions, competence of educational activity is formed and developed. Through the Hitori puzzle, future teachers will be able to expand their thinking by learning the basic features of the Hitori puzzle and teaching them to students.